Dorothea's eyes : Dorothea Lange photographs the truth - Rosenstock, Barb (Calkins Creek, an imprint of Highlights, 2016)
"In this powerful and inspiring book, Barb Rosenstock and Gérard DuBois reveal the story of [Dorothea Lange's] remarkable life and illuminate how her photographs continue to tell the world the truth."--